Financial barriers to oral cancer treatment in India. (March 2016) - Edwards, Patrick; Subramanian, Sujha; Hoover, Sonja; Ramesh, Chaluvarayaswamy; Ramadas, Kunnambath
Highlights: Treatment cost is now a lesser burden than non-medical costs associated with receiving oral cancer care at RCCs in India. Transportation, staying near a cancer center, and family/work duties are substantial burdens for RCC patients. There is a significant financial burden gap among patients with no education and those with primary or higher education. Abstract: The objective of this study was to determine the major financial barriers that affect people's access to oral cancer treatment in India. Barriers researched included not only the direct medical costs, but also the direct non-medical costs, such as transportation and lodging, and the indirect cost of missing work or family duties. Four hundred patients from two regions in southern India responded to a 2014 survey that asked about access and barriers to care. Traditionally, policies to increase screening, diagnosis and treatment of oral cancer have focused on affordable or free medical services for low-income groups; however, the hidden costs associated with receiving care are a significant burden. Transportation, lodging, loss of wages, and time away from family duties are key barriers to oral cancer care that policy makers should address.